Drivers of vehicle-to-everything (V2X) adoption: A behavioral reasoning theory perspective - Ibrahim Arpaci; Mohammed A. Al-Sharafi; Moamin A. Mahmoud (PLoS ONE, 2025)
Vehicle-to-Everything (V2X) is a critical technology that enhances safety, improves traffic efficiency, and paves the way for future vehicles, such as autonomous cars, by enabling vehicles to communicate with each other and their environment. This study investigated the relationships among the reasons for and against adopting V2X technology, environmental values, attitudes, intentions, and green behavior. Accordingly, a research model was developed based on “Behavioral Reasoning Theory” and validated through PLS-SEM, using data from electric vehicle (EV) drivers. The findings indicated that environmental values positively predict the reasons for V2X adoption, which positively predict attitudes toward V2X adoption. In contrast, environmental values negatively predict the reasons against V2X adoption, which negatively predict attitudes toward V2X adoption. These insights are crucial for understanding the dynamics that shape individuals’ attitudes toward V2X adoption and green behavior.